Capital Market Integration: Palestine and Israeli Experience. - Tulus Suryanto; Abdul Razak Abdul Hadi (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2015)
This study is driven by the motivation to examine the existence of probable equilibrium and dynamic relations between Palestine Stock Exchange (PEX) and Tel Aviv Stock Exchange (TASE). Within the framework of international trade theories, this study uses Engle-Granger Co-integration procedure as an estimation model employing monthly time series data during the observed period from January 1998 till February 2012. It was discovered that there is a significant equilibrium relationship between PEX and TASE, but no empirical evidence was found on the presence of dynamic relations between the two stock markets using Granger Causality tests. Meanwhile, analysis of dynamic interactions over post-sample period by Impulse-Response Functions and Variance Decomposition indicate that movements in TASE Index do influence the performance of PEX.DOI: 10.15408/aiq.v7i2.1697